Characterization of somatostatin receptors in guinea-pig isolated ileum, vas deferens and right atrium. - Feniuk, W. (Nature Publishing Group, 1993)
1. Somatostatin14 (SS14) inhibits neurogenically mediated contractile responses in guinea-pig ileum and vas deferens and exerts a direct negative inotropic action in guinea-pig spontaneously beating right atrium. In this study, the receptors mediating these inhibitory effects have been characterized by comparing the potencies of several cyclic somatostatin analogues. 2. In the guinea-pig ileum, SS14, somatostatin28 (SS28), somatostatin25 (SS25) and several smaller cyclic somatostatin analogues including octreotide, angiopeptin and CGP 23996, inhibited neurogenically mediated contractile responses, each being of similar potency. 3. In contrast, in the guinea-pig vas deferens and right atrium, SS28 was about 30 times more potent than SS14. However, although angiopeptin was nearly as potent as SS14 as an agonist in the vas deferens, in guinea-pig atrium angiopeptin had low intrinsic activity and antagonized the negative inotropic action of both SS14 and SS28 (pKB values of 7.4 and 7.2, respectively). CGP 23996 was 2-7 times weaker than SS14 in guinea-pig vas deferens and atria. 4. Phosphoramidon (1 microM) and amastatin (10 microM) did not influence the potency of SS14 or SS28 in either the guinea-pig ileum or right atrium. In the guinea-pig vas deferens, phosphoramidon and amastatin did not affect the potency of SS28, but enhanced the potency of SS14 about 5 fold. Despite the presence of phosphoramidon and amastatin, SS28 was still more potent than SS14 in the vas deferens. 5. The putative somatostatin receptor blocking drug, cyclo(7-aminoheptanoyl Phe-D-Trp-Lys-Thr[Brl]) (CPP; 1 microM), did not antagonize the effects of either SS14 or SS28 in ileum, vas deferens or atrial preparations.(ABSTRACT TRUNCATED AT 250 WORDS)